A bothremydid from the middle Cenomanian of Portugal identified as one of the oldest pleurodiran turtles in Laurasia. (October 2017) - Pérez-García, A.; Antunes, M.T.; Barroso-Barcenilla, F.; Callapez, P.M.; Segura, M.; Soares, A.F.; Torices, A.
Abstract: The relatively complete and well preserved shell of a turtle, from the middle Cenomanian of Nazaré (Portugal), is studied here. It is recognized as a member of the crown group Pleurodira and, more specifically, of Bothremydidae. Pleurodira are one of the two lineages of modern turtles, their origin being in Gondwana. Pleurodira are very abundant in the uppermost Cretaceous record of Europe. However, this new finding is one of the few occurrences in the lower Upper Cretaceous of Laurasia. A single member of Bothremydidae had so far been identified in Portugal: the late Campanian-early Maastrichtian Rosasia soutoi . It was the only Cretaceous turtle identified in that country both at specific and at generic levels, being exclusive of Portugal. The taxon from Nazaré is identified as Algorachelus peregrinus, this form is also present in the contemporaneous beds in Spain, and is the oldest member of Bothremydidae in Laurasia. Algorachelus peregrinus is confirmed here to be a coastal form, which facilitated its spread. The two oldest known bothremydids from Laurasia, the European A. peregrinus and the North American Paiutemys tibert, are compared for the first time. They are recognized as closely related taxa. This study provides new data allowing a more precisely characterization of the oldest so far known dispersal event of Pleurodira in Laurasia, which was performed by an African lineage of Bothremydidae that reached the east coast of the Atlantic Ocean at least in the middle Cenomanian, and the west region of that Ocean at least in the late Cenomanian. Highlights: A turtle shell from the middle Cenomanian of Nazaré (Portugal) is studied here. It corresponds to the second member of Bothremydidae identified in Portugal. It is one of the scarce bothremydid remains known in pre-Santonian Laurasian levels. It corresponds to Algorachelus, the oldest Bothremydidae in the Laurasian record. The oldest known dispersal event of Pleurodira to Laurasia is better understood.